Pengaruh Pelatihan dan Pengawasan Terhadap Kinerja Pegawai di Badan Kepegawaian dan Pengembangan Sumber Daya Manusia (BKPSDM) Kota Medan - Putri, Intan Sofiani Syah; Ekawati, Yuni Andri; Abdullah, Ujang (Excellent, 2025)
This study aims to examine the effect of training and supervision on employee performance at the Medan City Human Resources Development and Personnel Agency (BKPSDM). This study was designed with a causal type with a quantitative research approach. This study used subjects from the population, namely 89 employees at the Medan City Human Resources Development and Personnel Agency with a saturated sampling technique. The use of the Likert scale in this study. Data were analyzed using multiple regression techniques using the IBM Statistics SPSS Ver24 application. Training has a significant effect on Employee Performance at the Medan City Human Resources Development and Personnel Agency (BKPSDM); (2) Supervision does not have a significant effect on Employee Performance at the Medan City Human Resources Development and Personnel Agency (BKPSDM). (3) Training and Supervision have a significant effect on Employee Performance at the Medan City Human Resources Development and Personnel Agency (BKPSDM) with a contribution of only 25.5 percent.